Human milk IgA promotes normal immune development by limiting Th17-inducing Erysipelatoclostridium ramosum in the infant gut - Katherine Donald; Antonio Serapio-Palacios; Tahereh Bozorgmehr; Mandi Ma; Ma Andrea Isabelle Garcia; Charisse Petersen; Piushkumar Mandhane; Padmaja Subbarao; Theo J. Moraes; Elinor Simons; Stuart Turvey; Meghan B. Azad; et al. (Proceedings of the National Academy of Sciences, 2025)
The gut microbiota is highly dynamic during the first year of life and plays a crucial role in immune development. Breastfeeding is known to support infant health, but the contributions of the numerous breastmilk components to gut microbiota and immune maturation remain unclear. Secretory IgA (SIgA), the most abundant antibody in human milk, is a key modulator of gut microbiota composition. We have shown previously that mouse milk SIgA protects against asthma by limiting segmented filamentous bacteria in mice. The present study uncovers a similar mechanism in humans. Using human milk from the CHILD Cohort Study, we define a relationship between human milk SIgA and infant gut microbiota composition. This leads to the identification of Erysipelatoclostridium ramosum as a key player in immune development, which is controlled by milk SIgA. Cell culture modeling demonstrates that SIgA restricts the capacity of E. ramosum to adhere to the intestinal epithelium and to induce Th17 responses, which are implicated in allergic and other chronic diseases.